Preoperative hypoalbuminemia is an independent risk factor for conversion from laparoscopic to open cholecystectomy in patients with cholecystolithiasis. Issue 4 (9th June 2016) - Ishizuka, Mitsuru; Shibuya, Norisuke; Shimoda, Mitsugi; Kato, Masato; Aoki, Taku; Kubota, Keiichi
Abstract: Introduction: Laparoscopic cholecystectomy (LC) is regarded as the first choice for patients with cholecystolithiasis, but some patients require conversion to open cholecystectomy (OC) because of inflammation‐related incidents. Therefore, the aim of this study is to explore the risk factors for conversion to OC in patients undergoing elective LC for cholecystolithiasis. Methods: This study included 461 patients who underwent elective LC for cholecystolithiasis were between April 2000 and September 2010. Receiver–operator curve (ROC) analysis was used to define the ideal cut‐off values of clinicolaboratory characteristics, and the area under the ROC for conversion was also measured. Univariate and multivariate analyses using preoperative clinicolaboratory characteristics were performed to investigate the most significant risk factors for conversion to OC in patients with cholecystolithiasis. Results: Multivariate analysis using nine parameters selected by univariate analyses demonstrated that γ‐glutamyltransferase (< 20/>20 IU/L) (odds ratio, 8.777; 95% confidence interval, 1.132–68.06; P = 0.038), albumin (< 3.8/>3.8 g/dL) (odds ratio, 0.329; 95% confidence interval, 0.127–0.850; P = 0.022), and platelet count (< 27/>27 × 10 4 /mm 3 ) (odds ratio, 2.573; 95% confidence interval, 1.048–6.319; P = 0.039) were associated with conversion. Among these three parameters, ROC curve analysis disclosed that albumin (0.705) had the largest area under the ROC (γ‐glutamyltransferase, 0.622, platelet count, 0.536) for conversion. Conclusions: Preoperative hypoalbuminemia is the most important risk factor for conversion to OC in patients undergoing elective LC for cholecystolithiasis.